Clinical Examination and Validation of Primary Diagnosis in Anatomic Pathology Using Whole Slide Digital Images. - Jukić, Drazen M.; Drogowski, Laura M.; Martina, Jamie; Parwani, Anil V. (Archives of Pathology & Laboratory Medicine, 2011)
Context.--Novel anatomic pathology technologies allow pathologists to digitally view and diagnose cases. Although digital pathology advocates champion its strengths and move to integrate it into practice and workflow, the capabilities and limitations of digital slides have not been fully investigated. Objectives.-To estimate intrapathologist diagnostic discrepancy between glass and digital slides and to determine pathologists' diagnostic certainty when diagnosing with the 2 formats. Design.--Intrapathologist diagnostic consistency between glass and digital slides was measured. Three pathologists diagnosed 101 cases digitally and with corresponding glass slides. Discrepancies between formats were evaluated, and diagnostic precision and certainty were compared. Results.--A total of 606 diagnoses were evaluated in pairs (202 per pathologist). Seven cases did not transfer to the database and were eliminated from further study. We report no discrepancies between media in 75%, 87%, and 83% of the cases diagnosed by the 3 pathologists, respectively; significant discrepancies were identified in 3%, 3%, and 7% of cases by each pathologist. In total, we identified significant clinical and therapeutic discrepancies in 13 of 296 cases (4.4%). The certainty values provided by each pathologist were similar between formats. Conclusions.--This study did not detect significant differences between diagnoses based on digital and glass slides.We believe that this study further supports the integration of digital slides into pathology workflow, particularly considering the low rate of discrepancy documented here.